2002
DOI: 10.1007/bf03179846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on hyperlipidemic nephropathy under constant light exposure

Abstract: Studies have shown anti-hyperlipidemic actions of melatonin, with pharmacological doses inducing changes in cholesterol levels. This study was designed to evaluate the effect of melatonin on adriamycin-induced (25mg/kg b.w., i.p.) hyperlipidemia under constant light exposure. Melatonin was injected i.p. (1,000 microg/kg b.w./day). Triglycerides, total cholesterol, high-density lipoprotein cholesterol, light-density lipoprotein cholesterol, non-proteic nitrogen compounds (urea and creatinine levels), total prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…The renal dysfunction induced by this aminoglycoside was demonstrated by intense proteinuria and high blood urea nitrogen and creatinine concentration in plasma (table 4). These results are in accordance with other studies in which the nephropathies induced by different agents are related to oxidative stress (Guidet & Shan 1989;Yang et al 1995;Montilla et al 1997Montilla et al & 2000Montilla-Ló pez et al 1998;Walker et al 1999;Tú nez et al 2002Tú nez et al & 2003b. Additionally, these data are indirectly in agreement with studies which show that administration of antioxidants reduces nephrotoxicity induced by different agents (Ademuyiwa et al 1990;Ali & Bashir 1996;Erdem et al 2000;Kumar et al 2000;Ozbek et al 2000;Pedraza-Chaverri et al 2000;Maldonado et al 2003;Pedraza-Chaverri et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The renal dysfunction induced by this aminoglycoside was demonstrated by intense proteinuria and high blood urea nitrogen and creatinine concentration in plasma (table 4). These results are in accordance with other studies in which the nephropathies induced by different agents are related to oxidative stress (Guidet & Shan 1989;Yang et al 1995;Montilla et al 1997Montilla et al & 2000Montilla-Ló pez et al 1998;Walker et al 1999;Tú nez et al 2002Tú nez et al & 2003b. Additionally, these data are indirectly in agreement with studies which show that administration of antioxidants reduces nephrotoxicity induced by different agents (Ademuyiwa et al 1990;Ali & Bashir 1996;Erdem et al 2000;Kumar et al 2000;Ozbek et al 2000;Pedraza-Chaverri et al 2000;Maldonado et al 2003;Pedraza-Chaverri et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Different studies have shown that melatonin, an indoleamine, has neuro-and nephroprotective effects against experimental-induced oxidative stress in brain and kidney (Montilla-Ló pez et al 1998Benítez-King et al 2003;Montilla et al 2003;Tú nez et al 2002Tú nez et al , 2003a Moreover, the 5HT-depleting agent parachlorophenylalanine (PCPA) is frequently used to evaluate the role of the central serotoninergic system in the regulation of a number of physiological functions, including the secretion of renin by the kidney (Ikonomov et al 1990), the expression of inducible nitric oxide synthase (iNOS), neuronal NOS (nNOS) and nicotinamide adenine dinucleotide phosphate diaphorase (NADPHd) in brain (Ramos et al 2002). Furthermore, different reports suggest that serotonin (5HT) may have a relevant antioxidant activity (Ikonomov et al 1990;Liu & Mori 1993;Chan & Tang 1996;Daniels et al 1996;Matuszak et al 1997;Park et al 2002;Ramos et al 2002).…”
mentioning
confidence: 99%
“…In our study, these symptoms appeared to be affected by the photoperiod, which improved some of them in the darkness phase (AD+D vs AD), and made them worse in the permanent light phase (AD+L vs AD). Túnez et al [41] demonstrated that AD and constant light increased the triglyceride and cholesterol levels. These alterations were reverted toward normality by MEL administration, and this would seem to coincide with our results in which the darkness period with higher MEL values appears to improve the pathological symptoms of the AD-induced hyperlipidemic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…CETP decreased in some acute exercise studies [31], while LCAT increased acutely [32], and as it was mentioned above, melatonin may also increase the activity of this enzyme [30], which would lead to a decrease in the circulating cholesterol and may explain why total cholesterol decreases markedly with melatonin after intense physical exercise. The decrease in the plasma phospholipids levels underlines a significant antihyperlipidemic action of melatonin [33] which could be exerted also by increasing the clearance of endogenous cholesterol [34].…”
Section: Resultsmentioning
confidence: 99%